Viscoelastic Coupling Dampers for Enhanced Multiple Seismic Hazard Level Performance of High-Rise Buildings. Issue 4 (November 2018) - MacKay-Lyons, Renée; Christopoulos, Constantin; Montgomery, Michael
Viscoelastic coupling dampers (VCDs) are installed in lieu of traditional reinforced concrete (RC) coupling beams in high-rise buildings to provide distributed supplemental damping for all dynamic loading conditions without affecting the architectural layout. When distributed effectively over the height of the building, VCDs provide viscous damping in all lateral modes of vibration and an elastic restoring force that enhances the lateral stiffness of the coupled system. In this paper, a first extensive numerical case study is carried out to compare the seismic performance of a conventional coupled shear wall high-rise building to a high damping alternate of the same design in which VCDs replace all diagonal RC beams in the core to enhance its seismic resilience. The added damping from VCDs is intended to reduce the peak responses under low amplitude earthquakes, but for larger amplitude maximum credible earthquakes, the peak responses are similar; however, structural damage is greatly reduced. Three seismic hazard levels were investigated, and the results indicate that the use of VCDs reduces peak floor accelerations, story drifts, and story shears over all seismic intensities. Nonlinear time-history analysis results also highlighted the improved resilience of the VCD structure at the maximum credible seismic hazard level where the use of VCDs eliminated all damage to coupling beams that would otherwise require repair over most of the height of the building.